Identity Perceptions and Dynamics among Self-Identified Portuguese Bisexual Men: A Qualitative Study. Issue 3 (3rd July 2017) - Pereira, Henrique; Aparício, Beatriz; Borges, Mariana; Nave, Carina
ABSTRACT: Using the findings from a qualitative investigation based upon in-depth email surveys with 22 self-identified bisexual Portuguese men, this article explores bisexual identity perceptions and dynamics. Participants were asked to complete an online questionnaire with sociodemographic questions concerning, age, occupation, education, relationship status, sexual attraction, sexual behavior, and sexual fantasies in addition to an incorporated survey with 10 questions. The major findings were in regard to the following areas: identity definitions; stigma; coming-out issues; general obstacles; sexual activity; romantic involvement; social, familiar, or professional interactions; emotional well-being; and sexual orientation comparisons (bisexual men vs. gay or straight men). The article concludes by highlighting the negative and positive perceptions and dynamics of bisexual men, emphasizing that there is still a lot to be done regarding the affirmation of a consolidated bisexual community as a very important tool to fight discrimination against sexual minorities.